Real-Time Elastography of the Prostate. (22nd May 2014) - Junker, D.; De Zordo, T.; Quentin, M.; Ladurner, M.; Bektic, J.; Horniger, W.; Jaschke, W.; Aigner, F.
Abstract : Palpation of organs is one of the oldest clinical examination techniques, for instance, if you think of the palpation of the breast or the digital rectal examination of the prostate, where hard palpable regions are suspicious for cancer. This is the basic principle of real-time elastography, an ultrasound technique, which is able to visualise tissue elasticity. Since prostate cancer features an increased stiffness due to the higher cell and vessel density than the normal surrounding tissue, real-time elastography has been used for several years for prostate cancer detection. This review introduces the different techniques of ultrasound elastography and furthermore summarises its limitations and potentials.